Structural properties of Ga18Ge20.9Te61.2 alloys - Popovych, M.V.; Stronski, A.V.; Shprtko, K.V. (Physics and Chemistry of Solid State, 2022)
In this paper, amorphous Ga18Ge20.9Te61.2 alloys have been studied using the X-ray diffraction and Raman spectroscopy methods. The experimental X-ray diffraction patterns were used for calculations of radial distribution functions that indicate positions of the nearest-neighbour bond lengths r1 = 2.67 Å and second-neighbour bond length r2 = 4.27 Å. The similar r1-values were observed for Ga-Ge-Te glasses of other compositions. The bands observed in the Raman spectra of Ga18Ge20.9Te61.2 samples show that this glass contains different nanophases, which can be explained using the terms of vibration modes inherent to Ga-Te and Ge-Te glasses, as well as films. Investigations of compositional dependences of characteristic constituent Raman bands intensities, which change with the composition should be studied in order to obtain better assignment of Raman bands.